Apoptin causes apoptosis in HepG‐2 cells via Ca2+ imbalance and activation of the mitochondrial apoptotic pathway. (14th December 2022) - Yu, Xiaoyang; Wang, Tongxing; Li, Yue; Li, Yiquan; Bai, Bing; Fang, Jinbo; Han, Jicheng; Li, Shanzhi; Xiu, Zhiru; Liu, Zirui; Yang, Xia; Li, Yaru; et al.
Abstract: Background: Apoptin is derived from the chicken anemia virus and exhibits specific cytotoxic effects against tumor cells. Herein, we found that Apoptin induced a strong and lasting endoplasmic reticulum (ER) stress response, Ca 2+ imbalance, and triggered the mitochondrial apoptotic pathway. The aim of this study was to explore the mechanisms by which Apoptin exhibited anti‐tumor effects in HepG‐2 cells. Methods: The intracellular levels of calcium (Ca 2+ ) were induced by ER stress and determined by electron microscopy, flow cytometry, and fluorescence staining. The mitochondrial injury was determined by mitochondrial membrane potential and electron microscopy. Western blotting was used to investigate the levels of key proteins in ER stress and the apoptotic pathway in mitochondria. The relationship between Ca 2+ levels and apoptosis in Apoptin‐treated cells was analyzed using a Ca 2+ chelator (BAPTA‐AM), flow cytometry, and fluorescence staining. We also investigated the in vivo effects of Ca 2+ imbalance on the mitochondrial apoptotic pathway using tumor tissues xenografted on nude mice. Results: This study showed that Apoptin induced a strong and long‐ lasting ER stress and injury, which subsequently led to an imbalance of cellular Ca 2+ levels, a reduction in the mitochondrial membrane potential, a significant extent image in the mitochondrial structure, and an increase in the expression levels of Smac/Diablo and Cyto‐C. Conclusions: In summary, Apoptin induced apoptosis in HepG‐2 cells via Ca 2+ imbalance and activation of the mitochondrial apoptotic pathway. This study provided a new direction for antitumor research in Apoptin. Abstract : Apoptin induced a strong and long‐lasting ER stress and injury, which subsequently led to an imbalance of cellular Ca 2+ levels, a reduction in the mitochondrial membrane potential, a significant extent image in the mitochondrial structure, and an increase in the expression levels of Smac/Diablo and Cyto‐C.